RNA Sequencing Reveals Small and Variable Contributions of Infectious Agents to Transcriptomes of Postmortem Nervous Tissues From Amyotrophic Lateral Sclerosis, Alzheimer’s Disease and Parkinson’s Disease Subjects, and Increased Expression of Genes From Disease-Activated Microglia - Bennett, James P.; Keeney, Paula M.; Brohawn, David G. (Frontiers in Neuroscience, 2019)
Nervous tissues from both humans with neurodegenerative diseases (NDD) and animals with genetic models of human NDD, such as rare monogenic causes of Amyotrophic Lateral Sclerosis (ALS), Alzheimer’s disease (AD) and Parkinson’s disease (PD), show activated microglia, suggesting a potential causal role for inflammation in NDD. We performed paired-end (PE) RNA sequencing (RNAseq) of total RNA’s extracted from frozen sections of cervical spinal cords from ALS and CTL subjects, frontal cortices of AD and CTL subjects, and ventral midbrains of PD and CTL subjects. Trimmed PE reads were aligned against the hg38 human transcriptome using Tophat2/Bowtie2 and quantitated with Cufflinks. PE reads were also aligned using Bowtie2 against genomes from representative species of Toxoplasma gondii and Trichinella sp T6 (parasitic infectious agents), Babesia microtii and Borrelia burgdorferi (tick-vector borne agents), and Treponema denticola and Porphyromonas gingivalis, agents causing chronic gingivitis. Primary aligned reads of each agent in each tissue sample were quantitated with Samtools. We found small percentages (<0.1%) of transcriptomes aligned with B. microtii, B. burgdorferi, T. denticola and P. gingivalis genomes and larger percentages aligned with T. gondii (0.1-0.2%) and T. sp. 6 (1.0-1.1%) genomes. In AD specimens, but in no others, primary aligned transcriptome percentages, although small, approached significance for being greater in AD compared to CTL samples for B. burgdorferi (p=0.067) and P. gingvalis (p=0.068). Correlation tables of genes’ expressions in all three NDD’s revealed significant correlations among disease-associated microglial (DAM) genes in ALS, AD and PD. Infectious agents’ transcripts can be detected in RNAseq reads of both NDD and CTL tissues and vary from agent to agent. Expressions of Stage 1 and Stage 2 DAM genes significantly correlated with each other, suggesting the presence of Stages 1 and 2 DAM in our NDD tissue samples. (290 words)